1987
DOI: 10.1002/art.1780300711
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of infections among rheumatoid arthritis patients, before and after disease onset

Abstract: The self‐reported frequency of genitourinary and bronchopulmonary infections in postmenopausal women with rheumatoid arthritis (RA) and in postmenopausal women with osteoarthritis and/or soft tissue rheumatism was compared. Neither before, nor after the onset of joint disease was a higher frequency reported by the RA patients. The previously established increased mortality from infectious disease among RA patients might be due to a more severe infectious disease course, leading to an increased case‐fatality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 10 publications
3
12
0
2
Order By: Relevance
“…The possibility af an underestimation or an overestimation of the frequency of infections, particularly in view of the interview technique and the relatively short observation period, must be noted. Our results confirm those of an earlier Dutch study (8), which was restricted to middle-aged women, had a larger number of participating centers, and lacked verification of the diagnoses of infectious disease. Studies that have concentrated Qn mortality in patients with RA have revealed a high percentage of deaths due to infection (1,11,12).…”
Section: Frequency Of Infection Among Patients With Rheumatoid Arthrisupporting
confidence: 88%
See 2 more Smart Citations
“…The possibility af an underestimation or an overestimation of the frequency of infections, particularly in view of the interview technique and the relatively short observation period, must be noted. Our results confirm those of an earlier Dutch study (8), which was restricted to middle-aged women, had a larger number of participating centers, and lacked verification of the diagnoses of infectious disease. Studies that have concentrated Qn mortality in patients with RA have revealed a high percentage of deaths due to infection (1,11,12).…”
Section: Frequency Of Infection Among Patients With Rheumatoid Arthrisupporting
confidence: 88%
“…However, reports based on mortality data concern infections causing death, and do not take into account the overall frequency of infections occurring before and unrelated to the death. Comparative studies of the occurrence of infections in RA patients and control patients are scarce (7,8). One of these earlier analyses was also performed in The Netherlands (8), but the data used had been collected for a case-control study that was restricted to middle-aged women, and the infections reported were not verified medically.…”
Section: Frequency Of Infection Among Patients With Rheumatoid Arthrimentioning
confidence: 99%
See 1 more Smart Citation
“…A similar result was found in a previous study carried out by a group from Copenhagen, where a considerably high degree of associated non-obstructive pyelonephritis and renal papillary necrosis was detected among the renal autopsy materials from patients with RA (Clausen and Pedersen, 1961). However, this kind of association between RA and UTIs was not always observed (Vandenbroucke et al, 1987). This discrepancy in the results with an apparent lack of the epidemiological link between urinary www.intechopen.com infections and RA could be due to the occurrence of sub-clinical or occult infections, which are merely characterized by bacteriuria.…”
Section: Rheumatoid Arthritis and Urinary Tract Infectionssupporting
confidence: 63%
“…21 An incidence-based case control study of early RA suggested that prior blood transfusion might be a risk factor, 22 with the transfusion often happening several years previously. Subjects with new onset arthritis are no more likely to report immediately preceding infection than the general population, 23 but long latency from infection to disease onset might explain such a negative finding.…”
mentioning
confidence: 99%